Monetary policy and its stabilization role - Vlček, Jan (2007)
The thesis evaluates stabilization role of central bank in terms of robustness and sensitivity of optimal rules with respect to features of macroeconomic environment. To assess optimal rule properties consistently with current mainstream of monetary policy, it was necessary to develop and calibrate structural model and derive second order approximation of welfare loss. Based on these results the robustness and sensitivity of optimal rules was evaluated with respect to structural parameter changes and shock types.